2021
DOI: 10.3390/su13147834
|View full text |Cite
|
Sign up to set email alerts
|

Emission Characteristics of Hazardous Air Pollutants from Medium-Duty Diesel Trucks Based on Driving Cycles

Abstract: Studies on the characteristics of hazardous air pollutants (HAPs) in the emissions of medium-duty diesel trucks are significantly insufficient compared to those on heavy-duty trucks. This study investigated the characteristics of regulated pollutants and HAPs, such as volatile organic compounds (VOCs), aldehydes, and polycyclic aromatic hydrocarbons (PAHs), and estimated non-methane hydrocarbon (NMHC) speciation in the emissions of medium-duty diesel trucks. Ten medium-duty diesel trucks conforming to Euros 5 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…Literature has also indicated that, the processing of asphalt has the potentials of releasing high concentrations of harmful substances into the atmosphere [21,22,23]. Heavy-duty trucks, machines, and road construction can release significant amounts of poisonous gases and SPM into the environment [24,25,26]. Beer production processes have the capacity of polluting the environment including air with harmful substances [27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Literature has also indicated that, the processing of asphalt has the potentials of releasing high concentrations of harmful substances into the atmosphere [21,22,23]. Heavy-duty trucks, machines, and road construction can release significant amounts of poisonous gases and SPM into the environment [24,25,26]. Beer production processes have the capacity of polluting the environment including air with harmful substances [27,28,29].…”
Section: Introductionmentioning
confidence: 99%